EZH2: An analysis of a potential new tumor marker in high-risk localization of cutaneous squamous cell carcinomas - Valea, Cristian-Viktor; Klein, Maurice; Hallermann, Christian; Schulze, Hans-Joachim; Raguse, Jan-Dirk; Wermker, Kai (Frontiers in Oncology, 2025)
BackgroundEnhancer of zeste homolog 2 (EZH2) is a transcriptional enzyme implicated in tumor development and is often correlated to poor patient outcomes in various malignancies. The study evaluated various methods for EZH2 expression in lip and ear squamous cell carcinomas (LSCC, ESCC) by matching patients with and without lymph node metastasis (LNM) and further analysis of clinical outcome parameters. EZH2 inhibition therapy has shown promising results in multiple cancer entities, with ongoing research exploring its potential in other malignancies. This approach may also be applicable to high-risk LSCC and ESCC.MethodsA total of 122 patients who had been surgically treated for LSCC and ESCC were selected to form LNM-positive and LNM-negative matched pairs. EZH2 expression has been examined after immunostaining of the tumor tissue with EZH2-antibodies and quantified as extent, intensity, and score. Pursuing the clinical benefit, we analyzed three different EZH2-score approaches to determine aberrations in EZH2 expression.ResultsWhile the overall EZH2 extent did not correlate with clinical outcome, the EZH2-intensity and -score was lower in patients who developed a local relapse or distant metastasis (DM). High EZH2-scores correlated with increasing grading, pN-, and American Joint Committee on Cancer-stage. Overall, the carcinoma tissue samples showed a high expression of EZH2 (mean expression > 60%).ConclusionThe hypothesis of the predictive prognostic contribution of EZH2 in clinical decisions regarding the occurrence of LNM was not substantiated by our data. Nevertheless, the elevated expression of EZH2 we have observed in our findings could be utilized as a pretherapeutic assessment prior to targeted therapies with tazemetostat. Subsequent research should substantiate this hypothesis.